mTOR Promotes Survival and Astrocytic Characteristics Induced by Pten/Akt Signaling in Glioblastoma - Xiaoyi Hu; Pier Paolo Pandolfi; Yi Li; Jason A. Koutcher; Marc Rosenblum; Eric C. Holland (Neoplasia: An International Journal for Oncology Research, 2005)
Combined activation of Ras and Akt leads to the formation of astrocytic glioblastoma multiforme (GBM) in mice. In human GBMs, AKT is not mutated but is activated in approximately 70% of these tumors, in association with loss of PTEN and/or activation of receptor tyrosine kinases. Mechanistic justification for the therapeutic blockade of targets downstream of AKT, such as mTOR, in these cancers requires demonstration that the oncogenic effect of PTEN loss is through elevated AKT activity. We demonstrate here that loss of Pten is similar to Akt activation in the context of glioma formation in mice. We further delineate the role of mTOR activity downstream of Akt in the maintenance of Akt+KRas-induced GBMs. Blockade of mTOR results in regional apoptosis in these tumors and conversion in the character of surviving tumor cells from astrocytoma to oligodendroglioma. These data suggest that mTOR activity is required for the survival of some cells within these GBMs, and mTOR appears required for the maintenance of astrocytic character in the surviving cells. Furthermore, our study provides the first example of conversion between two distinct tumor types usually thought of as belonging to specific lineages, and provides evidence for signal transduction-mediated transdifferentiation between glioma subtypes.